The Contestation of Women’s Movement on Digital Media - Satiti, Nur Latifah Umi; Triastuti, Endah (Jogjakarta Communication Conference (JCC), 2025)
This paper aims to describe the contestation of women’s issue regarding sexual violence in digital media. The study focuses on how Aliansi Cinta Keluarga (Family Love Alliance/AILA) resists the discourse of anti-sexual violence. This research uses feminist postcolonial framework to describe how the contestation of discourse employed by AILA takes place through digital media. Postcolonial framework embraces diversity within the women's movement in the Global South. However, the scholarships aware that the acknowledgement towards diversity will be used by local elites to mask their domination which tends to marginalize women. Based on the assumption, the question offered is how AILA employs texts on digital media that contest women’s equity discourse in Indonesia. The research conducted digital ethnography for data collection. Data were collected through several methods, including observation on social media, webinars and off-line events. This research finds that AILA refuses gender equity discourse employed by feminist Muslim in Indonesia. They keep fighting feminist Muslim as they want to highlight their resistance as a form of difference. Furthermore, AILA, on one side, rejects western feminist discourse, yet, on the other side, they replicate the way western feminist reproduces the discourse.